Factorial structure of the sense of coherence and its relation with attachment - Ortiz-Granja, Dorys (2020)
The Sense of Coherence is formed by three factors: comprehensibility, manageability and meaningfulness. In this study, its factorial structure was analyzed through assessment with the SOC-29 scale and its relationship with attachment. Three hypotheses were proposed to assess the reliability, convergent validity and factorial structure, using a sample of 445 participants. Statistical analysis was based on descriptive techniques, Cronbach’s alpha, Pearson’s correlation and confirmatory factor analysis. The results obtained provide evidence in favor of the hypotheses, with an internal consistency of α=.82, a significant correlation with attachment r=.27 to .83 and an acceptable fit of the model χ2=1275.88, CFI=.85, RMSEA=.07 [.06-.07], SRMR=.04. The study highlights the importance of the linguistic changes made to adapt the scale to the Ecuadorian context. Two important limitations are mentioned regarding its application as a self-report and the geographical location, which need to be taken into consideration in subsequent studies. © 2020 Instituto Brasileiro de Avaliacao Psicologica. All rights reserved.